Bioaccessibility of antioxidants and fatty acids from Fucus spiralis - Francisco, João (2020)
Fucus spiralis is an edible brown seaweed (SW) found in the Portuguese Coast. It has been reported to have high antioxidant activity, which may elicit a potential use for the food industry. However, little information is available on how the SW behaves during the digestive process and how the freeze-drying process might affect the bioaccessibility of the di erent compounds. Therefore, antioxidant activity, total polyphenols, lipid, and fatty acid contents were measured before and after in vitro simulation of the human digestive process, both in fresh and freeze-dry SW. F. spiralis had a lipid content of 3.49 +- 0.3% of dry weight (DW), which is a usual amount described for this SW genus. The total lipid bioaccessibility was 12.1 +- 0.1%. The major omega-3 fatty acid detected was eicosapentaenoic acid, 7.5 +- 0.1%, with a bioaccessibility percentage of 13.0 +- 1.0%. Four different methods—total phenolic content (TPC), ferric reducing antioxidant power (FRAP), oxygen radical absorbance capacity (ORAC), and 1,1-diphenyl-2-picryl-hydrazyl (DPPH)—were used to assess the antioxidant activity of F. spiralis. The bioaccessibility of the antioxidants studied, ranged between 42.7% and 59.5%, except the bioaccessibility of polyphenols in freeze-dried SW (23.0% +- 1.0%), suggesting that the freeze-drying process reduces the bioaccessibility of these compounds.